Bird Census Data Do Not Indicate a Lack of Impact on Songbirds From the Growth of Avian Predator Populations in Britain in the Late 20th Century - Bell, Christopher Paul (Frontiers in Ecology and Evolution, 2020)
The possible role of avian predators in limiting songbird populations has been largely discounted since the publication of findings showing a lack of statistical association in UK bird census data between changes in prey species populations and those of a range of predatory species, including raptors and corvids. I re-applied the methodology behind these findings, covering a wider range of prey species and using site-level modelling to estimate predator abundance instead of a mixture of spatial modelling and raw count data. A significant aggregate predator effect was found in 33 out of 40 prey species, compared to only 10 out of 27 in the original study, as well as a higher rate of significant individual predator effects, with 41 significantly negative and 84 significantly positive effects out of a total of 320. The greater explanatory power of predator variables estimated using site-level modelling suggests that this has significant advantages over the use of predator variables derived from spatial modelling, which may not capture variation in predator abundance at a local scale, or from raw count data, which may lead to attenuation of effect estimates. The prevalence of positive associations between predators and prey is consistent with a common response to local habitat variation, which may absorb negative covariance resulting from the impact of predators on prey populations. Both positive and negative predator-prey associations may also occur as a result of independent demographic processes that manifest as sequential habitat occupation or withdrawal. Analyses of census data cannot discriminate among these possible scenarios and may therefore have limited value in determining whether predators have been limiting prey populations. Inference to a lack of impact of avian predators on prey populations from such analyses may therefore be unsafe, and a role for increased predator numbers remains a viable hypothesis with respect to bird population declines. The recent neglect of this possibility should therefore be urgently reversed, with a particular need for field experiments that can support strong inference regarding population limitation of songbirds by avian predators.